Is diet partly responsible for differences in COVID‐19 death rates between and within countries?. Issue 1 (27th May 2020) - Bousquet, Jean; Anto, Josep M.; Iaccarino, Guido; Czarlewski, Wienczyslawa; Haahtela, Tari; Anto, Aram; Akdis, Cezmi A.; Blain, Hubert; Canonica, G. Walter; Cardona, Victoria; Cruz, Alvaro A.; Illario, Maddalena; et al.
Abstract: Reported COVID‐19 deaths in Germany are relatively low as compared to many European countries. Among the several explanations proposed, an early and large testing of the population was put forward. Most current debates on COVID‐19 focus on the differences among countries, but little attention has been given to regional differences and diet. The low‐death rate European countries (e.g. Austria, Baltic States, Czech Republic, Finland, Norway, Poland, Slovakia) have used different quarantine and/or confinement times and methods and none have performed as many early tests as Germany. Among other factors that may be significant are the dietary habits. It seems that some foods largely used in these countries may reduce angiotensin‐converting enzyme activity or are anti‐oxidants. Among the many possible areas of research, it might be important to understand diet and angiotensin‐converting enzyme‐2 (ACE2) levels in populations with different COVID‐19 death rates since dietary interventions may be of great benefit.